Efeito agudo de diferentes configurações de alongamento em idosos corredores - Patricia Hampe Mio Lisboa (2013)
The population has aged considerably in Brazil and, there is an increasingly search for physical activity by elderly individuals. In this context, it is common amateurs elderly runners seeking professionals and monitoring of the area for training or sports injury treatment. Then comes the need for clarification as to how conduct senior athletes with physical training and therapeutic interventions, specifically on interventions stretching. This study is a randomized trial that compared the effects of different stretching configurations at maximum range of motion (ROMmax) on the reduction of passive resistance torque (Torque PR). The sample consisted of 15 elderly, aged at 60 years and more, practicing running with no history of recent injuries. They underwent three stretching interventions and a control evaluation on different days: constant torque intervention with four repetitions of 120s (CT120), constant torque intervention with four repetitions of 30s (CT30), constant angle intervention with four repetitions of 120s (CA120) and a control evaluation. All interventions showed significant differences in gain and a reduction in ROMmax RP torque compared to the control condition (p<0,04). The CT120 intervention produced greater gain in ROMmax and torque RP compared to CT30 and CA120 (p=0,042 and p=0,049) Interventions CT30 and CA120 showed no significant differences in the effects. The study concludes that the protocol of stretching CT120s produces greater gains than CT30 and CA120, although all have significant effects compared to baseline values.